THE EFFECT OF MICROCLIMATE MODIFICATION AND ORGANIC FERTILIZER MATERIALS ON THE PHYSIOLOGICAL ACTIVITY OF KATOKKON CHILI (Capsicum chinense jacq.) - Putri Ramadhan N.L; Yulinda Tanari; Martin Pangli (Agropet, 2026)
ABSTRACT Katokkon chili pepper (Capsicum chinense Jacq.) is a high-value horticultural crop whose productivity is influenced by microclimate conditions and nutrient availability. This study aimed to evaluate the effects of 70% shade netting, bokashi fertilizer made from guano, Gliricidia sepium, and Senna siamea, and their interaction on the physiological activity of Katokkon chili pepper. A Split Plot Design was used with two shade levels as the main plots and five bokashi doses (0, 25, 50, 75, and 100 g/polybag) as the subplots, replicated three times. The results showed that 70% shade netting improved the microclimate and increased plant fresh and dry weight. Bokashi significantly affected transpiration rate, leaf chlorophyll content, and plant dry weight, while the interaction significantly affected only leaf chlorophyll. Overall, combining 70% shade netting with 75–100 g/polybag bokashi produced the best plant growth response. Keywords: 70% Shade Netting, Bokashi, Chlorophyll.